THE METHOD OF IMPARTING DESIRED FILTERING PROPERTIES FOR CLOSED-LOOP CONTROL SYSTEM - A. G. Strizhnev (Системный анализ и прикладная информатика, 2017)
This article presents a method of imparting desired filtering properties for closed-loop control system. The method is based on using of input rate limiter and synthesis of special digital controllers within ideal low-pass filters. Synthesis of the controllers was made using third-order astatic plant and different ideal low-pass filters. Considering the control objects saturation zone and required bandwidth, input rate limiter was calculated. The digital modeling and comparative analysis are applied. The author offered practical guidelines for using results of investigation.